IMPLEMENTASI PINJAMAN TUNDA TEBANG HUTAN RAKYAT DI KABUPATEN BLORA DAN KABUPATEN WONOSOBO, PROVINSI JAWA TENGAH - Duhita Herlyn Lusiya; Dudung Darusman; Nunung Nuryartono (Jurnal Penelitian Sosial dan Ekonomi Kehutanan, 2020)
Loan for delaying timber harvesting known as Pinjaman Tunda Tebang (PTT) launched by the government to help forest farmer in order to fulfill their needs. This program is designed to delay the harvesting of young trees till can reach the cycle age for optimum sustainability and economic value. The study aims to determine farmer’s understanding and loan implementation based on PTT principle in Blora and Wonosobo Regencies by using quantitative approach and descriptive statistics analysis. Data collection was carried out through interviews and questionnaires to 222 respondents. The results showed that understanding of the debtor farmers are among others: the loan process is complicated and time-consuming, lack of commitment to the contract, useful loan, and satisfy with loan mechanism compared to middlemen. Implementation of PTT related to the “appropriate subject” and “appropriate location” is in accordance with the provisions. However, there is still disobedience to some commitments, such as “appropriate activity” commitment by harvesting the collateral tree before the contract ended, non-smooth repayment of loans by some farmers on the “appropriate disbursement and repayment” commitment. The study recommends: a) bureaucratic and procedural mechanisms improvement to accelerate the process, precise, and useful; b) improvement of rules or procedures related the harvesting due to force majeure such as pest and disease attack and its protection, field assistants, as well as  field technical guidance, especially  the resilience of tree label.